Clinical Characteristics of Dogs with Progressive Myelomalacia Following Acute Intervertebral Disc Extrusion. (29th September 2017) - Castel, A.; Olby, N.J.; Mariani, C.L.; Muñana, K.R.; Early, P.J.
Abstract : Background: Progressive myelomalacia (PMM) is a catastrophic disease associated with acute intervertebral disc extrusion (IVDE). Published data on the clinical characteristics of this disease are limited. Objective: To describe the onset and progression of clinical signs of PMM in a large case cohort. Animals: Fifty‐one dogs, 18 with histopathologically confirmed PMM, 33 presumptively diagnosed based on clinical signs and diagnostic imaging. Methods: Retrospective study. Dogs with confirmed IVDE and either a histopathologic diagnosis of PMM or a high clinical suspicion were identified by medical record search. Data on nature and progression of signs were extracted. Results: Twenty‐four of 51 dogs were Dachshunds. T12–T13 was the most common site of disc extrusion (12 of 56), and 18 of 55 of mid‐to‐caudal lumbar discs (between L3 and L6) were affected. Onset of PMM signs ranged from present at first evaluation (17/51) to 5 days after presentation, with 25 of 51 cases developing signs within 48 hours. Progression of signs from onset of PMM to euthanasia or death, excluding 7 cases euthanized at presentation, ranged from 1 to 13 days with 23 being euthanized within 3 days. Nonspecific systemic signs were documented in 30 of 51 dogs. Conclusion and Clinical Importance: The majority of dogs developed PMM within 2 days of presentation and was euthanized within another 3 days. However, onset can be delayed up to 5 days after presentation with progression to euthanasia taking as long as 2 weeks. Mid‐to‐caudal lumbar discs might be associated with an increased risk of PMM.